Factors Influencing Individual Behavior: A Comprehensive Analysis of Personal Conduct - Farfieva, Komola Athamdjanovna (International Journal of Formal Education, 2024)
The literature on individual behavior offers a comprehensive examination of the interplay between biological, psychological, and social influences. Key studies highlight the role of personality traits, genetic factors, and situational contexts in shaping personal conduct. Research reveals that decision-making processes are heavily influenced by social norms and environmental conditions, with social identity and intrinsic motivations playing pivotal roles in pro-environmental behavior. Additionally, innovations in personality assessment suggest that non-standardized methods are needed to capture the complexity of individual behavior. Together, these studies underscore the need for an interdisciplinary approach to understanding the multifaceted nature of behavior, emphasizing the integration of biological predispositions, social environments, and cognitive processes.